Assessment of Postresuscitation Volume Status by Bioimpedance Analysis in Patients with Sepsis in the Intensive Care Unit: A Pilot Observational Study - Bram Rochwerg; Jason H. Cheung; Christine M. Ribic; Faraz Lalji; France J. Clarke; Susheel Gantareddy; Nischal Ranganath; Aziz Walele; Ellen McDonald; Maureen O. Meade; Deborah J. Cook; Trevor T. Wilkieson; et al. (Canadian Respiratory Journal)
Background. Bioimpedance analysis (BIA) is a novel method of assessing a patient’s volume status. Objective. We sought to determine the feasibility of using vector length (VL), derived from bioimpedance analysis (BIA), in the assessment of postresuscitation volume status in intensive care unit (ICU) patients with sepsis. Method. This was a prospective observational single-center study. Our primary outcome was feasibility. Secondary clinical outcomes included ventilator status and acute kidney injury. Proof of concept was sought by correlating baseline VL measurements with other known measures of volume status. Results. BIA was feasible to perform in the ICU. We screened 655 patients, identified 78 eligible patients, and approached 64 for consent. We enrolled 60 patients (consent rate of 93.8%) over 12 months. For each 50-unit increase in VL, there was an associated 22% increase in the probability of not requiring invasive mechanical ventilation (IMV) (p=0.13). Baseline VL correlated with other measures of volume expansion including serum pro-BNP levels, peripheral edema, and central venous pressure (CVP). Conclusion. It is feasible to use BIA to predict postresuscitation volume status and patient-important outcomes in septic ICU patients. Trial Registration. This trial is registered with clinicaltrials.gov NCT01379404 registered on June 7, 2011.